(untitled) (Scientific journal of the Fergana State University, 2026)
This article presents a scientific and philosophical analysis of the interconnection between ancient religious traditions and folk medicine. It explores the spiritual and moral foundations of healing in Zoroastrianism, Buddhism, and Manichaeism, as well as their influence on the development of Islamic medical thought. The harmony between religious values and medicine is examined through the scholarly heritage of prominent Islamic thinkers such as Abu Ali Ibn Sina, Abu Bakr al-Razi, and al-Farabi.